Changes in the quality of sour milk curds with candied fruit and dry licorice root during storage : ст. - Nagovska, V. O.; Bilyk, O. Ya.; Slyvka, N. B.; Mykhaylytska, O. R. (Stepan Gzhytskyi National University of Veterinary Medicine and Biotechnologies, 2023)
In recent years, there has been a scientific interest in healthy nutrition, namely the development and consumption of products. which have a beneficial effect on the human body and can reduce the risk of various diseases. The work aimed to investigate the change in the quality of sour milk curds with candied fruit and dry licorice root during storage. The research was carried out at the Ivano-Frankivsk DP, as well as in the laboratory of the Department of Technology of Milk and Dairy Products of the Stepan Gzhytskyi National University of Veterinary Medicine and Biotechnologies Lviv. When determining the titrated acidity in curds with candied fruit without licorice root during the storage period at a temperature of 4 ± 2 °C, it increases from 200 °T to 230 °T. In sour milk curds with candied fruit and dry licorice root, the titrated acidity on the first day of storage was 220 °C T, and on the fifth day – 230 °T. Since, according to the standard, fermented milk curds with candied fruit can be stored for no more than 3 days, based on the conducted research, we conclude that the newly made curds are entirely safe for consumption during the above period. Analyzing the microbiological indicators of newly created sour milk curds with candied fruit and dry licorice root, we can conclude that this product is harmless to health, as its sanitary condition meets the standard's requirements. Thus, using dry licorice root in producing sour milk curds with candied fruit as a non-dairy additive does not impair the microbiological indicators of this type of curd.
Keywords: fermented milk products; кисломолочні сирки